Sitagliptin Stimulates Endothelial Progenitor Cells to Induce Endothelialization in Aneurysm Necks Through the SDF-1/CXCR4/NRF2 Signaling Pathway - Yu, Guo; Liu, Peixi; Shi, Yuan; Li, Sichen; Liu, Yingjun; Zhu, Wei (Frontiers in Endocrinology, 2019)
Aneurysm (AN) embolization is an important treatment for cerebral aneurysms. The endothelialization of the aneurysm neck is crucial for preventing aneurysm recurrence. Sitagliptin is a therapeutic drug for diabetes that has been reported to have cardiovascular-protective effects. This study investigated the effect of sitagliptin on endothelial progenitor cell (EPC) function and endothelialization of aneurysm necks after embolization. The effect of sitagliptin on aneurysm neck endothelialization was examined using a rat aneurysm embolization model. We isolated EPCs and used CCK-8 (Cell Counting Kit-8) and annexin V/PI to analyze the effect of sitagliptin on the proliferation and apoptosis of EPCs. The effects of sitagliptin on the migration and invasion of EPCs were examined using scratch and Transwell assays. The effect of sitagliptin on the angiogenic ability of EPCs was examined using a sprouting assay. Western blot analysis and ELISA were used to analyze the effect of sitagliptin on the expression of proangiogenic factors in EPCs. The in vivo results indicated that sitagliptin promoted endothelialization of the aneurysm neck and increased circulating EPCs and expression levels of SDF-1 and VEGF in peripheral blood. Sitagliptin promoted the proliferation, migration, invasion and angiogenic abilities of EPCs. Western blot analysis and ELISA showed that sitagliptin promoted the expression of SDF-1 and VEGF in progenitor endothelial cells. Western blot assays showed that sitagliptin activated the expression of NRF2, which is dependent on the function of CXCR4. Furthermore, sitagliptin promoted progenitor endothelial cell migration, invasion and angiogenesis through the SDF-1/CXCR4/NRF2 signaling pathway. Additionally, progenitor endothelial cells expressed SDF-1 and VEGF. The promotion of endothelialization by sitagliptin provides an additional therapeutic option for preventing the recurrence of AN.